A heterozygous p.S143P mutation in LMNA associates with proteasome dysfunction and enhanced autophagy-mediated degradation of mutant lamins A and C - West, Gun; Turunen, Minttu; Aalto, Anna; Virtanen, Laura; Li, Song-Ping; Heliö, Tiina; Meinander, Annika; Taimen, Pekka (Frontiers in Cell and Developmental Biology, 2022)
Lamin A/C are nuclear intermediate filament proteins that form a proteinaceous meshwork called lamina beneath the inner nuclear membrane. Mutations in the LMNA gene encoding lamin A/C cause a heterogenous group of inherited degenerative diseases known as laminopathies. Previous studies have revealed altered cell signaling pathways in lamin mutant patient cells, but little is known about the fate of mutant lamin A/C within the cells. Here, we analyzed the turnover of lamin A/C in cells derived from a dilated cardiomyopathy patient with a heterozygous p.S143P mutation in LMNA. We found that transcriptional activation and mRNA levels of LMNA are increased in the primary patient fibroblasts, but that the lamin A/C protein levels remain equal in control and patient cells because of a meticulous interplay between autophagy and the ubiquitin-proteasome system (UPS). Both endogenous and ectopic expression of p.S143P lamin A/C cause significantly reduced activity of UPS and accumulation of K48-ubiquitin chains in the nucleus. Furthermore, K48-ubiquitinated lamin A/C is degraded by compensatory enhanced autophagy, as shown by increased autophagosome formation and binding of lamin A/C to microtubule-associated protein 1A/1B-light chain 3. Finally, a chaperone 4-PBA augmented protein degradation by restoring UPS activity as well as autophagy in the patient cells. In summary, our results suggest that the p.S143P mutant lamin A/C has overloading and deleterious effects on protein degradation machinery and pharmacological interventions with compounds enhancing protein degradation may be beneficial for cell homeostasis.